Brokerage and Social Capital in the Prehispanic U.S. Southwest. Issue 2 (17th May 2013) - Peeples, Matthew A.; Haas, W. Randall
ABSTRACT In social network analysis, brokerage refers to the processes through which individuals or larger groups mediate interactions between actors that would otherwise not be directly connected. Brokers occupy key intermediate positions that have alternately been interpreted as sources of social capital or potential disadvantages. Recent empirical studies suggest that the relationship between brokerage and rewards or risks varies considerably depending on the nature of interactions in a given setting. In this study, we use a large settlement and ceramic database including sites across the western U.S. Southwest (C.E. 1200–1400) to identify settlements that likely filled brokerage roles in ceramic networks. We develop a new structural measure of brokerage and compare long‐term outcomes for settlements characterized by varying degrees of brokerage. We argue that brokerage was not a major source of social capital in our study area, as interactions instead favored the formation of discrete groups over such intermediate positions.